PERBANDINGAN EKONOMI ADAT MINANGKABAU DENGAN EKONOMI ISLAM - Yunimar Yunimar (IAIN Batusangkar, 2019)
Years Ago, the Minangkabau tribe Community in West Sumatera as the the largest matrilineal in the world, has a communal economic system based on the Minangkabau tradition with a proto-democratic system. This paper aims to analyze the comparison of traditional economies with Islamic economics. The research method is descriptive qualitative by conducting surveys and focused group discussion (FGD). The results show Minang people who obey the Islamic rules and Minang custom do not carry out the Islamic economy system. It is because the influence of social and cultural side such as the capitalist economy system. As a result, there will be less togetherness between people based on the philosophy of